2013
DOI: 10.1002/masy.201300019
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of Long‐Chain Branching in Ziegler‐Natta Polyethylene Homopolymers as Studied via SECMALS and Rheology

Abstract: Summary Comprehensive polymer architectural studies were carried out on a group of Ziegler‐Natta (Z‐N) polyethylene homopolymers via size‐exclusion chromatography coupled with multi‐angle light scattering (SEC‐MALS) and rheology. Although Z‐N resins are traditionally viewed as linear polymers, both SEC‐MALS and rheology results strongly indicate that there are topological variations, presumably long‐chain branching (LCB) or possibly hyper‐branches, in this group of supposedly linear Z‐N homopolymers. These Z‐N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…Ziegler–Natta HDPE grades are traditionally viewed as the definition of linear polymers. However, recent experimental results clearly indicate the presence of long‐chain branches in certain Z–N HDPE grades . Polymer fractions with a high long‐chain branching content, were detected in the high molecular weight tail of HDPE produced in a slurry‐phase process.…”
Section: Sample Simulation Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ziegler–Natta HDPE grades are traditionally viewed as the definition of linear polymers. However, recent experimental results clearly indicate the presence of long‐chain branches in certain Z–N HDPE grades . Polymer fractions with a high long‐chain branching content, were detected in the high molecular weight tail of HDPE produced in a slurry‐phase process.…”
Section: Sample Simulation Results and Discussionmentioning
confidence: 97%
“…Finally, it should be noted that the proposed kinetic mechanism includes a terminal double bond reaction resulting in the formation of LCB. Latest developments in polymer characterization (i.e., gel permeation chromatography multi‐angle light scattering (GPC‐MALLS)) and increased accuracy of rheological measurements of industrial polyethylene grades have revealed that under certain conditions (i.e., catalyst, high hydrogen concentration and production of low molecular weight polyethylene), the formation of long chain branches in HDPE is possible …”
Section: Catalytic Olefin Copolymerization Kinetic Mechanism and Specmentioning
confidence: 99%
“…Their M w and η 0 values were determined by GPC and creep test, respectively, where . The relationship between η 0 and M w for linear PE (Figure B) was obtained as log η 0 = −13.99 + 3.58 log M W , which was consistent with that reported in the literature . The creep test curves for sample Control_2 and samples runs 6–8 are shown in Figure A, and the obtained η 0 and M w data are introduced into Figure B.…”
Section: Resultsmentioning
confidence: 99%
“…[14] SEC-FTIR has also been used to quantify the overall branching content as a function of molar mass. [15] The analytical characterization of LCB includes 13 C NMR [16,17] , rheology [18][19][20] and high-temperature SEC with MALLS [21,22] or with triple detection. [23] While NMR and rheology enable to obtain an average content of LCB, SEC-MALLS enables to estimate the distribution of LCB along the molar mass axis.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical characterization of LCB includes 13 C NMR, rheology and high‐temperature SEC with MALLS or with triple detection . While NMR and rheology enable to obtain an average content of LCB, SEC‐MALLS enables to estimate the distribution of LCB along the molar mass axis.…”
Section: Introductionmentioning
confidence: 99%